Pengaruh Penggunaan ChatGPT Terhadap Kemampuan Peserta Didik Kelas XII MAN 1 Kota Padang dalam Menyelesaikan Tugas - Habib Hidayatul Rizki; Taza Nur Ahziha; Reda Lillah; Gusmaneli Gusmaneli (Jurnal Pendidikan Sosial Dan Konseling, 2025)
This research aims to determine the effect of using ChatGPT on the ability of Grade XII students at MAN 1 Kota Padang in completing academic tasks. The study employs a descriptive qualitative approach, with data collected through open-ended questionnaires distributed to students. The collected data were analyzed to explore how ChatGPT influences students’ understanding of the material, task completion speed, and the quality of their academic work. The results reveal that all respondents were familiar with and had used ChatGPT as a learning aid. Most students reported using ChatGPT frequently or very frequently, particularly to help them understand lessons and complete assignments more efficiently. The use of ChatGPT has been shown to positively affect time efficiency, comprehension, and the quality of students’ work. However, students also demonstrated critical awareness by verifying the information obtained, indicating that their dependence on the technology remained moderate. Overall, the use of ChatGPT has a positive and significant impact on students’ ability to complete academic tasks. The integration of ChatGPT into the learning process effectively supports students’ digital literacy and learning outcomes, though teacher supervision remains essential to ensure its use does not diminish critical thinking skills or originality in student work.